2008
DOI: 10.1080/10586458.2008.10129026
|View full text |Cite
|
Sign up to set email alerts
|

The 2-adic Valuation of Stirling Numbers

Abstract: We analyze properties of the 2-adic valuations of the Stirling numbers of the second kind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 10 publications
3
48
0
Order By: Relevance
“…This gives an alternative proof of the Amdeberhan conjecture [5] which was proved in [8]. Thus ν(S(n + 1, k + 1)) = σ(k) − σ(n) iff S(n, k) is a MZC, in which case ν(S(n + 1, k + 1)) = ν(S(n, k)).…”
Section: Basic Properties Of the Estimates And Cases Some Examples Amentioning
confidence: 80%
“…This gives an alternative proof of the Amdeberhan conjecture [5] which was proved in [8]. Thus ν(S(n + 1, k + 1)) = σ(k) − σ(n) iff S(n, k) is a MZC, in which case ν(S(n + 1, k + 1)) = ν(S(n, k)).…”
Section: Basic Properties Of the Estimates And Cases Some Examples Amentioning
confidence: 80%
“…Furthermore, they found that the 2-adic valuation of the Stirling numbers of second kind of order 5 is the first non-trivial case. In fact, they showed that v 2 (S(4n + 1, 5)) = v 2 (S(4n + 2, 5)) = 0 for all natural numbers n. It was also observed in [1] that v 2 (S(4n, 5)) = v 2 (S(4n + 3, 5)) for most indices. Consequently, Amdeberhan, Manna and Moll proposed a conjecture describing those indices n such that v 2 (S(4n, 5)) = v 2 (S(4n + 3, 5)).…”
Section: Introductionmentioning
confidence: 93%
“…Amdeberhan, Manna and Moll [1] studied the 2-adic valuations of Stirling numbers of second kind. Actually, they computed the 2-adic valuation v 2 (S(n, k)) for k ≤ 4.…”
Section: Introductionmentioning
confidence: 99%
“…The number that counts this process of division of a set in disjoint sets that go from 2 to k is the Stirling number of the second type. In this way, the number of configurations of the space of solutions of CaRS is at least O(2 n ) greater than the space of solutions of the Traveling Salesman Problem, since that for k = 2 the associated number of Stirling is O(2 n ) (Amdeberhan et al 2008). For a general case of CaRS the dimension of the space of solutions is still greater once there is not a theoretical limit for the number of different cars to be considered in the problem.…”
Section: The Difficulty Of Solving Carsmentioning
confidence: 99%